Fundamental principles of Christian teaching in the «Divine Comedia»: The reception of Thomas Aquinas in Dante’s work - Bártoli, Mariano (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
«Tu duca, tu signore, e tu maestro». These words begin an educational relationship between Virgil and Dante that concretely manifests a vision of the teacher of permanent validity and relevance. Dante’s journey allows us to discover in the Divina Comedia the existence of universal principles on which the teacher’s action is based. However, these principles are not entirely original, but they also reveal the influence that Thomas Aquinas has exerted on Dante. Aquinas is not only mentioned in Paradise in cantos X to XIV, but Thomistic pedagogical principles, especially those contained in the Summa Theologiae, inform the concrete relationship between the two poets. In this study we will try to make explicit the vision of the master proposed by Dante, while seeking to show that Thomas Aquinas is the main source from which Dante draws in order to forge this specific relationship between master and disciple.
Keywords: Thomas Aquinas; Theacher; Dante Alighieri; Providence; Theaching; Education; Divina Comedia